A review of the corrective power of personal comfort systems in non-neutral ambient environments. (September 2015) - Zhang, Hui; Arens, Edward; Zhai, Yongchao
Abstract: This paper discusses a spectrum of systems that cool or heat occupants personally, termed 'personal comfort systems' (PCS), in order to quantify their ability to produce comfort in ambient temperatures that are above or below the subjects' neutral temperatures. The comfort-producing effectiveness may be quantified in terms of a temperature difference, coining the index 'corrective power' (CP). CP is defined as difference between two ambient temperatures at which equal thermal sensation is achieved - one with no PCS (the reference condition), and one with PCS in use. CP represents the degree to which a PCS system may "correct" the ambient temperature toward neutrality. CP can alternatively be expressed in terms of thermal sensation and comfort survey scale units. Published studies of PCS are reviewed to extract their CP values. Cooling CP ranges from −1 to −6 K, and heating CP from 2K to 10 K. The physical characteristics of the particular PCS systems are not reported in detail here, but are presented as prototypes of what is possible. Deeper understanding of PCS will require new physiological and psychological information about comfort in local body segments and subsegments, and about spatial and temporal alliesthesia. These topics present many opportunities for productive future research. Highlights: 'Personal comfort systems' (PCS) heat/cool occupants independent of HVAC systems. 'Corrective power' (CP) quantifies effectiveness of PCS. Published studies of PCS are reviewed to extract their CP values. Cooling CP ranges from −1 to −6 K, and heating CP from 2 K to 10 K. The paper summarizes the fundamental psychophysical basis underlying PCS comfort.